Rāmacandra Tarkālaṅkāra, Muktārāma Bidyābāgīsa, Giriśacandra Bidyāratna, Lālāmohana Bidyānidhi - Bāndyopādhyāẏa, Brajendranātha (Baṅgīya-Sāhitya-Pariṣad, 1960)
Inhalt: Kurzbiographien d. Bengali-Schriftsteller Rāmacandra Tarkālaṅkāra (1793-1845), Muktārāma Bidyābāgīsa (?-1860), Giriśacandra Bidyāratna (1822-1903), Lālāmohana Bidyānidhi (1845-1916)
Keywords: Biografie